2018
DOI: 10.1111/jhn.12569
|View full text |Cite
|
Sign up to set email alerts
|

Advancing practice in dietitians’ communication and nutrition counselling skills: a workplace education program

Abstract: To our knowledge, this is the first dietitian-specific workplace education program of its type to address essential skills for better communication with patients. Ongoing workplace support, such as peer observation, is recommended to assist with skill development and sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…These overlap with descriptions of emotional intelligence capabilities in the literature, suggesting that emotional intelligence is related to reasoning dimensions in dietitian CDM 51‐54 . Students and practising clinical dietitians tend to focus on clinician–patient communication and associated skills with education appropriately focused on developing these skills 55,56 . However, emotional intelligence skills are yet to emerge as prominent components of the communication skill professional development programmes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These overlap with descriptions of emotional intelligence capabilities in the literature, suggesting that emotional intelligence is related to reasoning dimensions in dietitian CDM 51‐54 . Students and practising clinical dietitians tend to focus on clinician–patient communication and associated skills with education appropriately focused on developing these skills 55,56 . However, emotional intelligence skills are yet to emerge as prominent components of the communication skill professional development programmes.…”
Section: Discussionmentioning
confidence: 87%
“…[51][52][53][54] Students and practising clinical dietitians tend to focus on clinician-patient communication and associated skills with education appropriately focused on developing these skills. 55,56 However, emotional intelligence skills are yet to emerge as prominent components of the communication skill professional development programmes. Therefore, dietitians encountering medical dominance and the acute care setting's inherit complexity are more likely to be capable of engaging in influential communication if they possess adequate amounts of emotional intelligence and interpersonal skills.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described training programs for students and dietitians that focused on, or included components of relationship development. 53,58,65,80 One study described a training program designed to teach 'relationship-establishing skills' to nutrition students and thus appeared focused on the relationship itself. 65 In contrast, other studies listed the relationship as a component of training programs but often focused on different skill aspects of relationship development, such as counselling or communication skills.…”
Section: Resultsmentioning
confidence: 99%
“…Dietitians have reported that further training in communication skills is essential post‐qualification . Current evidence suggests that there is variation in the standard of communication skills in practice and as an important part of developing competence is exposure to competent performance, this may hinder effective teaching and assessment in the practice setting .…”
Section: Discussionmentioning
confidence: 99%